The Effect of The Ratio of Blood Shells (Andara Granosa) and Natural Fibers to The Bending Strength of The Composite - Utami, Arum Vania (ROTASI, 2021)
Particle board composites that uses fiber as alternative to meet the needs of wood which is significant increase while forest resources can not meet it. The manufacture of fiber boards experienced instability in several quarters of 2015, in the first quarter 82,30 thousand m3 of fiber boards were produced and continued to experience a significant increase per year. In addition, increasing amount of waste palm fiber and coconut fiber also causes problems for the environment. This research aims to determine the effect of ratio of blood shells (Anadara granosa) and natural fibers to the bending strength of the composite. In this research used hand lay up method or manual printing by pressing the mold according to free variable i.e. fiber type with volume fraction 0:30, 20:10, 15:15, and 10:20 (%v). Obtained a composite with coconut fiber has the greatest average bending strength when the volume fraction ratio of blood shells and coconut fiber 0:30 is equal to 39,57 MPa, while the composite with palm fiber has the greatest average bending strength when the fraction ratio 10:20 volume of 39,57 MPa.